The Indian Uterary Paradigm and its Role in the Orlentaust Program of Western Episteme - Jaskūnas, Valdas (Acta Orientalia Vilnensia, 2001)
The article deals with the problem of literary orientalism which is explored in perspective of postorientalist studies showing the essential role of Western literary idiosyncrasy in the program of knowledge and interpretative strategies of Indian culture. Giving a brief survey of interest in Indian literary culture among British orientalists and German Romanticists during the period from the end of 18th to the beginning of 19th centuries, our research is intended to show the influence of literary idiosyncrasy as central methodological strategy of Western scholarship on the construction and argumentation of the orientalist discources of literature, religion, and colonial domination. For this purpose the author discusses the first translations of Indian poetical texts and their interpretations which while applying the hermeneutic models of Western scholarship enabled the orientalists to construct the textual canons of Indian traditions as well as the intellectual history of India itself. Consequently, methodological europeanization of Indian traditions explains the leading role of orientalist literary paradigm in the formation of eurocentric Western episteme and the establishing of its hegemonic power both in India and Europe.